2019
DOI: 10.1111/bcpt.13210
|View full text |Cite
|
Sign up to set email alerts
|

Management of pharmacotherapy‐related problems in acute coronary syndrome: Role of clinical pharmacist in cardiac rehabilitation unit

Abstract: Acute coronary syndrome (ACS) is one of the leading causes of mortality worldwide and negatively impacts healthcare costs, productivity and quality of life. Polymorbidity and polypharmacy predispose ACS patients to medication discrepancies between cardiologist‐prescribed medication and drug use by the patient, drug‐related problems (DRPs) and inadequate drug adherence. This study aimed to evaluate the impact of clinical pharmacist–provided services on the outcome of ACS patients. This was a prospective, random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 41 publications
1
32
0
5
Order By: Relevance
“…Foram feitas 138 intervenções no grupo teste, indicado como controlar os efeitos colaterais dos fármacos (44,2%), adição de medicamentos (20,2%), suspensão de medicamentos (8%), substituição de medicamentos (14 %) e ajuste de dose (14%), tendo uma aceitação de 96,2%. As classes mais relacionadas com os PRMs, em ambos os grupos, teste e controle, foram: Beta-bloqueadores (21,9%), estatinas (17,3%) e IECA/ARBs (15,3%) (Casper et al, 2019).…”
Section: Importância Do Farmacêutico Na Redução Dos Prmsunclassified
See 1 more Smart Citation
“…Foram feitas 138 intervenções no grupo teste, indicado como controlar os efeitos colaterais dos fármacos (44,2%), adição de medicamentos (20,2%), suspensão de medicamentos (8%), substituição de medicamentos (14 %) e ajuste de dose (14%), tendo uma aceitação de 96,2%. As classes mais relacionadas com os PRMs, em ambos os grupos, teste e controle, foram: Beta-bloqueadores (21,9%), estatinas (17,3%) e IECA/ARBs (15,3%) (Casper et al, 2019).…”
Section: Importância Do Farmacêutico Na Redução Dos Prmsunclassified
“…Os PRMs podem serem resultantes das etapas que envolvem o processo terapêutico, como a prescrição, dispensação e administração, mas também do efeito nocivo que pode ser esperado no tratamento. A ocorrência dos PRMs, prejudica a farmacoterapia e podem causar danos aos pacientes (Nascimento et al, 2020), esse resultado diferente do que é almejado na terapêutica, provoca consultas extras e hospitalizações, o que colabora com o aumento nos custos de saúde (Casper et al, 2019). Os efeitos nocivos ao paciente desenvolvido da terapia, constitui as reações adversas a medicamentos ou erros de medicação (EM), caracterizando os PRMs (Aguiar et al, 2018).…”
Section: Introductionunclassified
“…A retrospective study showed that MDT-based cardiac rehabilitation with clinical pharmacist involvement improved adherence to ACE inhibitors and beta-blocker therapy and decreased rates of readmission [41]. Furthermore, clinical pharmacist involvement in cardiac rehabilitation was associated with a reduction in drug-related problems in a randomized trial, as well as improvements in medication adherence, patient knowledge regarding secondary prevention of ACS, and health-related quality of life [42]. Similarly, in a prospective real-world study, hospital-based rehabilitation with clinical pharmacist involvement led to improvements in physical and mental health at 1-year post-discharge [43].…”
Section: Cardiac Rehabilitationmentioning
confidence: 99%
“…Deste modo, promover a educação em saúde do paciente e propor intervenções sobre regimes terapêuticos ao serem conduzidas por farmacêuticos se apresentam como boas estratégias para a melhoria da efetividade do tratamento e para redução de discrepâncias medicamentosas, sendo assim implementadas na prática clínica visando-se à otimização e racionalização da farmacoterapia e à segurança do paciente (RAVN-NIELSEN et al, 2018;BRANCO et al, 2019;CASPER et al, 2019;RODRIGUES et al, 2019).…”
Section: Introductionunclassified